2007
DOI: 10.1080/13556509.2007.10799239
|View full text |Cite
|
Sign up to set email alerts
|

Recontextualization of News Discourse

Abstract: This paper explores the translation of news discourse in terms of the way in which recontextualization of discourse across the boundaries of language, culture and institutions results in the transformation, as well as transfer, of information. Based on a comparative analysis of news stories on North Korea published in Newsweek and Newsweek Hankuk Pan (Korean edition), the study examines how North Korea is (re)constructed in translation. The primary focus is on the translating context and the producers of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(22 citation statements)
references
References 9 publications
0
18
0
4
Order By: Relevance
“…Greenall and Løfaldli (2019) have recently applied this notion to translation studies as an alternative to the widely used 'adaptation' since, in their view, recontextualization can contribute to studying multisemiotic transfers by focusing on medial, generic, cultural, ideological and linguistic elements. Initially proposed by Bernstein (1990), recontextualization could prove a very productive concept in future research on the transformations and effects of journalistic translation, as shown by the work of Ji-Hae Kang (2014) on Korean news translation, Hernández Guerrero (2010) on interviews in the Spanish daily El Mundo and Floros (2012) on the translated news items dealing with conflicts in the Greek context.…”
Section: Discourse and Linguistic Approaches In Journalistic Translationmentioning
confidence: 99%
“…Greenall and Løfaldli (2019) have recently applied this notion to translation studies as an alternative to the widely used 'adaptation' since, in their view, recontextualization can contribute to studying multisemiotic transfers by focusing on medial, generic, cultural, ideological and linguistic elements. Initially proposed by Bernstein (1990), recontextualization could prove a very productive concept in future research on the transformations and effects of journalistic translation, as shown by the work of Ji-Hae Kang (2014) on Korean news translation, Hernández Guerrero (2010) on interviews in the Spanish daily El Mundo and Floros (2012) on the translated news items dealing with conflicts in the Greek context.…”
Section: Discourse and Linguistic Approaches In Journalistic Translationmentioning
confidence: 99%
“…Entre los estudios revisados predominan aquellos que analizan la transmisión de mensajes provenientes de países asiáticos, como China, Corea del Norte o Irán, hacia Occidente. Kang (2007) analizó el conflicto entre ideologías diversas que supone la recontextualización del discurso político de las noticias sobre Corea del Norte. Por su parte, Shojaei y Laheghi (2012) hacen el análisis crítico del discurso político de las noticias traducidas por el periódico iraní jaam-e-jam y discuten cómo la ideología política puede modificar el sentido de las traducciones.…”
Section: Comunicación Global Ideologías Nacionales Y Traducciónunclassified
“…Ji-hae Kang (2007) plantea que "la traducción periodística es una práctica compleja, por el conflicto entre las diversas representaciones e ideologías en torno a la política internacional, sumado a los objetivos y procedimientos de cada institución" (p. 219). Este planteamiento se evidencia en la traducción de la Agencia Andina.…”
Section: Reencuadre De Factores Económicosunclassified
“…Translation and evaluation may also be viewed as a process of complex interplay. Based on her analysis of certain English articles, their translations into Korean and their final revised translations, Kang (2007) draws the conclusion that the translators' choices and the editors/evaluators' ones can be viewed as a result of a complicated interplay of translators' and editors/evaluators' subjectivities, which are founded on their interpretations of the original text, institutional objectives and well-defined norms (p. 240).…”
Section: Definition and Conceptmentioning
confidence: 99%